Unintended Beneficiaries: Examining 3 kg LPG Consumption Among Upper-Middle-Class Households in Bali - Pardita, Dewa Putu Yudi; Purnami, Anak Agung Sri; Putra, I Komang; Darma, I Ketut (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: This study investigates the consumption patterns and awareness of 3 kg LPG subsidy policies among upper-middle-class households in Bali, a relatively unexplored area in energy subsidies and consumer behavior.Research Objectives: To examine the effects of income, price, and practicality on awareness and consumption of 3 kg LPG and evaluate whether awareness mediates these relationships.Research Methods: A mixed-methods approach combines quantitative survey data with qualitative interview insights. Structural Equation Modeling (SEM) analyzes quantitative relationships, while qualitative findings provide contextual depth.Empirical Results: Income does not affect awareness, while price and practicality had a significant positive impact. However, income, price, and practicality had adverse but insignificant effects on 3 kg LPG consumption. Awareness did not mediate the relationships between income, price, practicality, and consumption.Implications: Policymakers should improve subsidy distribution, strengthen public education campaigns, and promote alternatives like induction stoves to reduce dependence on subsidized LPG. JEL Classification: D12, H23, L95, Q41, Q48